Contesting orientations: Measure construction and the prediction of sportspersonship. (September 2015) - Shields, David Light; Funk, Christopher D.; Bredemeier, Brenda Light
Abstract: Objective: This three-study investigation was undertaken to develop, validate, and test the Contesting Orientations Scale (COS), a new measure designed to assess individuals' tendencies to use contest-is-partnership and contest-is-war conceptual metaphors (i.e., contesting orientations) when competing (Shields & Bredemeier, 2009, 2011a). Design: The research design was correlational. Following preliminary item creation and expert review, survey based studies were conducted to develop theoretically-based, psychometrically sound scales measuring contesting orientations. Method: In Study 1, an exploratory factor analysis (EFA) was performed on a preliminary 39-item COS administered to a sample of high school athletes (N = 233). Study 2 used EFA to evaluate a revised 23- item COS with a second sample of high school athletes (N = 92) resulting in a final reduction of the measure to twelve items. Confirmatory factor analysis (CFA) was then conducted on this 12-item COS, which proved an excellent fit to the data. A new sample of college athletes (N = 238) allowed Study 3 to (a) further examine the factorial validity of the COS, including gender invariance testing, (b) assess the concurrent validity of the COS via its correlations with goal orientations, empathy, moral identity, and moral disengagement; and, (c) assess the COS's incremental predictive utility for investigations of sportspersonship. Results and conclusion: Results from the sequence of studies demonstrate that the 12-item, two-scale COS has good psychometric properties as assessed through EFA and CFA, good concurrent validity, and adds significantly to existing measures in the prediction of sportspersonship. Highlights: Contesting orientations are metaphor-based interpretations of the meaning of contests. Two primary metaphors (partnership and war) structure understandings of contesting. A measure of contesting orientation is developed and validated. Contesting orientation adds predictive utility to investigations of sportspersonship.